Asupan Zat Gizi Makro dan Mikro terhadap Kejadian Stunting pada Balita - Ayuningtyas Ayuningtyas; Demsa Simbolon; Ahmad Rizal (Politeknik Kesehatan Tanjung Karang, 2018)
Stunting is a cumulative process and is caused by insufficient intake of nutrients or recurrent infectious diseases or both. Stunting can also occur before birth and is caused by very poor nutritional intake during pregnancy, eating patterns that are very lacking, low quality of food in line with the frequency of infectious diseases so that it can inhibit growth (UNICEF, 2012). This type of research was descriptive analytic. The study design was cross-sectional consisting of 58 samples of toddlers 24-59 months in the work area of Sumber Urip Health Center Rejang Lebong Regency in 2018. Data were collected in the form of nutritional status data TB/U using microtoice tools, energy intake, macro and micronutrients using questionnaires 2x24 hour recall. Toddlers 24-59 months who experienced stunting were 17 people (29.3%) and normal ones were 41 people (70.7%). The incidence of stunts was largely due to a lack of energy intake, and zinc. The results of this study indicate that there was a significant relationship between energy intake, macronutrients, and zinc with the incidence of stunting in infants.